Phytochemical Evaluation and Plant Regeneration Through Somatic Embryogenesis of Ferulago angulata subsp. Carduchorum (Boiss. and Hausskn), an Endangered Medicinal Plant - HA Naghdi Badi; Sh Salek Hashemi; AA Nasrollahnezhad Qomi; Saeed Navabpour; A Qaderi (Institue of Medicinal Plants, ACECR, 2017)
Background: Ferulago angulata is an important medicinal plant and endemic to Iran which is an endangered Plant. Objective: The aim of this study was to achieve an efficient method for propagation of this plant and evaluation of essential oil content and composition in habitat. Metthods: Essential oils were extracted by hydrodistillation using Clevenger-type apparatus and its composition was analyzed by the GC and GC-MS. For callus induction, explants were cultured on MS medium supplemented with NAA, 2,4-D and BA. For somatic embryogenesis, the calli were cultured on MS medium supplemented with full, 1/4 and 1/10 fold of growth regulators and MS medium without growth regulator. For maturation, embryogenic clumps were transferred on MS medium supplemented with BA, 2,4-D and 30 or 60 g l-1 sucrose. The small embryogenic clumps were transferred to medium with GA3. Results: The main components of essential oils were Ocimene (29.84%), followed by α-pinene (27.01%), Isobornyl formate (7.7%) and gamma-Terpinene (4.85%). The highest percentage of callus induction observed in the root and hypocotyl explants. The maximum somatic embryogenesis was obtained in MS medium with 0.5 mg l-1 2, 4-D via hypocotyls derived explants. The highest frequency of maturation was obtained in MS medium containing 30 g l-1 sucrose without growth regulators. Conclution: This plant had a noticeable amount of essential oil with valuable ingredients and tissue culture techniques could be applied for its mass propagation, conservation of germplasm and in vitro regeneration.